Deriving Dual Dimensions of Bias: Preposed Negation Questions with EVEN. (22nd October 2020) - Jeong, Sunwoo
Abstract: Polar interrogatives with preposed negation (e.g., Didn't Cam help? ) convey positive epistemic bias. Polar interrogatives with even -type expressions, including prosodically stressed NPIs and minimizer NPIs (e.g., Did Cam lift a finger to help? ), convey negative epistemic bias and often have a rhetorical flavor. This paper examines hybrid PQ constructions with both preposed negations and even -type expressions (e.g., Didn't Cam lift a finger to help? ; henceforth even -PNQs). It first presents a series of experimental studies which reveal that even -PNQs are characterized by complex, dual dimensions of bias contributed compositionally by both the preposed negation on the one hand and the even -type expression on the other. It then explores the theoretical implications of these results. The emerging data are shown to impose certain constraints on and generate additional desiderata for both the analyses of preposed negation questions and the analyses of even -type questions. Building on this discussion, a compositional analysis of even -PNQs is proposed. The analysis supports the presence of inner vs. outer negation ambiguity in PNQs, and identifies even -PNQs as inner-negation PNQs. It also adopts an informativity-based approach to the meaning contribution of even, formulated around the settledness of alternative issues.